Human lipocalins bind and export fatty acids through the secretory pathway of yeast cells - Ekim Kocabey, Aslihan; Schneiter, Roger (Frontiers in Microbiology, 2024)
The activation of fatty acids to their acyl-CoA derivatives is a crucial step for their integration into more complex lipids or their degradation via beta-oxidation. Yeast cells employ five distinct acyl-CoA synthases to facilitate this ATP-dependent activation of acyl chains. Notably, mutant cells deficient in two of these fatty acid-activating (FAA) enzymes, namely Faa1 and Faa4, do not take up free fatty acids but rather export them out of the cell. This unique fatty acid export pathway depends on small, secreted pathogenesis-related yeast proteins (Pry). In this study, we investigate whether the expression of human fatty acid-binding proteins, including Albumin, fatty acid binding protein 4 (Fabp4), and three distinct lipocalins (ApoD, Lcn1, Obp2a) could promote fatty acid secretion in yeast. To optimize the expression and secretion of these proteins, we systematically examined various signal sequences in both low- and high-copy number plasmids. Our findings reveal that directing these fatty-acid binding proteins into the secretory pathway effectively promotes fatty acid secretion from a sensitized quadruple mutant model strain (faa1∆ faa4∆ pry1∆ pry3∆). Furthermore, the level of fatty acid secretion exhibited a positive correlation with the efficiency of protein secretion. Importantly, the expression of all human lipid-binding proteins rescued Pry-dependent fatty acid secretion, resulting in the secretion of both long-chain saturated and unsaturated fatty acids. These results not only affirm the in vitro binding capabilities of lipocalins to fatty acids but also present a novel avenue for enhancing the secretion of valuable lipidic compounds. Given the growing interest in utilizing yeast as a cellular factory for producing poorly soluble compounds and the potential of lipocalins as platforms for engineering substrate-binding specificity, our model holds promise as a powerful tool for promoting the secretion of high-value lipid-based molecules.